Pengaruh Etos Kerja dan Disiplin Kerja terhadap Dinas Kearsipan dan Perpustakaan Kabupaten Sikka - Hiasinta Claurita Insani; Andreas Rengga; Yustina Olivia Da Silva (Universitas Nusa Nipa Maumere, 2023)
This research is grounded on an issue that employee performance at the archives and Library Office in Sikka Regency. This research aimed to (1) know the description of employee performance, work ethic, and work discipline; and (2) analyse work ethic and work discipline on employee performance both partially and simultaneously.The population in this research were employees of the Archives and Library Office in Sikka Regency as many as 30 people. This research was conducted by census or saturated sampling because the population was limited. Data were collected through questionnaries and analysed through descriptive and inferential statiscal methods, namely multiple linear regression. Hypothesis testing was done through the F-test and t-test.The results of descriptive analysis showed and the variables of employee performance, work ethic, and work discipline were categorized as good. The result of the t-test statistic showed that partially the work ethic and work discipline variables have no effect on employee performance. The result of the F-test showed that simultaneously all independent variables have a significant effect on employee performance. The result of the determination analysis showed that the two independent variables in this studye are able to explain the variation in the ups and downs of employee performance.